2017
DOI: 10.1002/ccr3.878
|View full text |Cite
|
Sign up to set email alerts
|

A case of HIV‐negative plasmablastic lymphoma of the bone marrow with a unique immunophenotype

Abstract: Key Clinical MessageWe present an interesting case of plasmablastic lymphoma, which is a rare type of non‐Hodgkin lymphoma that is typically diagnosed in HIV‐positive patients and has an immunophenotype that overlaps with multiple myeloma. Our patient is unique because he is HIV‐negative, has primary bone marrow disease, and has an atypical immunophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…PBL has a characteristic immunophenotype, where in they are positive for the plasma cell markers such as CD38, CD138, and MUM1; and negative for the typical B-cell antigens such as CD20 and CD79 [6,9]. As the pathological examination of our case showed that CD38, CD138 and MUM1 markers were positive and CD20 and CD79 were negative.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…PBL has a characteristic immunophenotype, where in they are positive for the plasma cell markers such as CD38, CD138, and MUM1; and negative for the typical B-cell antigens such as CD20 and CD79 [6,9]. As the pathological examination of our case showed that CD38, CD138 and MUM1 markers were positive and CD20 and CD79 were negative.…”
Section: Discussionmentioning
confidence: 46%
“…Clinically, HIV-positive patients have a stronger male predominance, early lifetime onset, and classically manifest with EBV positive oral cavity lesions. Additionally, HIV-positive patients with PBL respond to antiretroviral medications and have improved overall survival [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations